Can electric vehicle drivers be persuaded to eco-drive? A field study of feedback, gamification and financial rewards in Germany. (May 2020) - Günther, Madlen; Kacperski, Celina; Krems, Josef F.
Highlights: Driving data from a 22 months long-term naturalistic driving study in Germany were analysed. Persuasive strategies led to a reduced energy consumption in electric vehicles. Gamification elements promoted the strongest decrease in energy consumption. Long-term usage of persuasion resulted in the persistence of practising eco-driving. Driving experience predicted eco-driving knowledge. Abstract: Promoting eco-driving with battery electric vehicles (BEVs) can help drivers reduce their average energy consumption and enhance the driving range of a BEV. The present study examined the influence of three persuasive strategies (feedback regarding energy consumption, gamification, and financial rewards) compared to a baseline condition (no feedback or intervention) on the average BEV energy consumption under natural driving conditions. The influence of persuasive strategies on participants' attitudes towards eco-driving, as well as self-reported eco-driving knowledge were investigated. The persuasive strategies were used over 22 months. 108 participants took part in the field study in Germany and used BEVs for their daily business travel. Energy consumption data was gathered via data loggers. Participants had unlimited access to their post-drive eco-driving feedback via a web application. The use of game design (i.e. gamification) elements and financial rewards significantly reduced energy consumption as compared to baseline or mere feedback regarding energy consumption. Participants showed a habituation to eco-driving after removal of the strategies. Driving experience with BEV and gamification predicted eco-driving knowledge. We found first evidence from a highly naturalistic field trial by providing driving data from a car sharing case study, improving on previous studies that mostly used laboratory settings or instructed driving. We expanded upon persuasion research, supporting the idea that gamification can be strongly relevant for energy saving behaviour.